Effect of the tunneled-cuffed central venous catheters on oxidative stress indices and inflammation in chronic hemodialysis patients - Korucu, Berfu; Yeter, Hacı Hasan; Bali, Elif Burcu; Derici, Mehmet Kürşat (The European Research Journal, 2021)
Objectives: The use of central venous catheters as hemodialysis (HD) vascular access is associated with worse morbidity and mortality in HD patients. This occasion is often attributed to comorbidities of the patients with central venous catheters. Studies reveal that a biofilm layer occurs on most of the tunneled-cuffed central venous catheters (TC-CVCs). This study aimed to determine the oxidative stress (OS) and systemic inflammation (SI) status in patients with TC-CVCs as HD vascular access without clinical signs and symptoms of infection. Methods: The study is composed of eighty-five patients with a minimum HD vintage of one year. Patients with a history of infection or a cardiovascular event within six months, malignancy, systemic inflammatory diseases, or malnutrition were excluded. OS indices and SI markers were studied and compared in patients with arteriovenous fistula (AVF) and TC-CVCs. Results: Mean native thiol/total thiol (NT/TT) ratio was significantly higher and mean disulphide/total thiol (DT/TT) ratio was significantly lower in AVF group comparing TC-CVC group (0.46 ± 0.17 and 0.36 ± 0.17, p = 0.03 for NT/TT; 0.27 ± 0.08 and 0.31 ± 0.08, p = 0.04 for DS/TT; respectively). Mean OS index was significantly lower in the AVF group comparing TC-CVC group (0.15 ± 0.14 and 0.24 ± 0.23, p = 0.04; respectively]. Median hs-CRP levels and median IL-6 levels were significantly lower in AVF group comparing TC-CVC group (5.8 [min: 3.0-max: 82.5] mg/L and 9.7 [min: 3.0-max: 45.4] mg/L, p = 0.004 for hs-CRP; 6.2 [min: 2.0-max:159.0] pg/mL and 12.2 [min: 2.6-max: 41.3) pg/mL, p = 0.01 for IL-6; respectively). Conclusions: TC-CVCs inversely affect OS and systemic inflammatory status in HD patients, presumably due to foreign body reactions and biofilm layers.